(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate the cost / benefit ratio and the economic viability of the green fertilizer consortium in conilon coffee (Coffea canephora). The experiment consisted of five consortiums (treatments) of coffee with legumes, namely: coffee + pigeon pea (Cajanu cajans L.); coffee + black mucuna (Stizolobium aterrimum); coffee + pork beans (Canavalia ensiformis); Mexican coffee + daisy (Tithonia diversifolia) and single coffee (weed soil). Evaluations were made on 10 coffee plants per treatment. The experiment was carried out in a lane, with the planting of legumes between the lines. Total Cost CT = CFT + CVT, Operating cost COP = CT - CO, Average fixed cost CFMe = CFT / Q, Average variable cost CVMe = CVT / Q, Average total cost CTMe = CT / Q, Average operating cost CopMe = COp / Q, Total gross income RBT = PxQ, Total net income RLT = RBT - CT, Net operating income Rlop = RBT - COP, Profitability RT = RLT / Investment x 100, Profitability LC = RLT / RBTx100, Leveling point PN = CT / market price, Safety margin MS = RBT / RBTx100. The treatment that stood out was the Mexican Margaridão, presenting higher net income in economic activity, allowing an oscillation both in the production and in the commercialization of the coffee bag, being the most recommended. In the second year of evaluation, in general, green manure, presented a better profitability and having a better production compared to the other treatments. In the three years of experiment, green fertilizers provided greater production in comparison to the Witness treatment, with emphasis on the Mexican Margaridão, in the years 2017 and 2018.